Early Onset of Combined Oxidative Phosphorylation Deficiency in Two Chinese Brothers Caused by a Homozygous (Leu275Phe) Mutation in the C1QBP Gene - Wang, Jie; Li, Huan; Sun, Min; Yang, Ying; Yang, Qianli; Liu, Bailing; Liu, Fang; Hu, Wen; Zhang, Yanmin (Frontiers in Pediatrics, 2020)
Mitochondrial diseases constitute a group of heterogeneous hereditary diseases caused by impairments in mitochondrial oxidative phosphorylation and abnormal cellular energy metabolism. C1QBP plays an important role in mitochondrial homeostasis. In this study, clinical, laboratory examinations, 12-lead electrocardiographic, ultrasonic cardiogram, and magnetic resonance imaging data were collected from four members of a Chinese family. Whole exome were amplified and sequenced for the proband. The structure of protein encoded by the mutation was predicted using multiple software programs. The proband was a 14-year old boy with myocardial hypertrophy, exercise intolerance, ptosis, and increased lactate. His 9-year old brother exhibited similar clinical manifestations while the phenomenon of ptosis was not as noticeable as the proband. The onset of this disease was in infancy in both cases. They were born after uneventful pregnancies of five generation blood relative Chinese parents. A homozygous mutation (Leu275Phe) in the C1QBP gene was identified in both brothers in an autosomal recessive inherited pattern. Their parents were heterozygous mutation carriers without clinical manifestations. We demonstrated that a homozygous C1QBP- P.Leu275Phe mutation in an autosomal recessive inherited mode of inheritance caused early onset combined oxidative phosphorylation deficiency 33 (COXPD 33) (OMIM：617713) in two brothers from a Chinese family.